2019
DOI: 10.1159/000496202
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis, Management, and Outcome of Fetal Subdural Haematoma: A Case Report and Systematic Review

Abstract: <b><i>Background:</i></b> Fetal subdural haematoma (SDH) is associated with poor prognosis. <b><i>Objective:</i></b> The conflicting evidence from the literature presents a challenge in prenatal counselling. We present a case study and systematic review of the literature for the management and outcome of fetal SDH. <b><i>Methods:</i></b> Systematic search of electronic database. <b><i>Results:</i></b> A total 45 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…So far, only a few reports are similar to our case. 2,6,8,12,15 This reversed flow has been reported as a rare finding related to pathological fetal conditions, such as fetal growth restriction, 3,4,7,10,11,13 fetomaternal hemorrhage, 1,5,9 and congenital hydrocephalus. 14 Some cases had a transient period of reversed flow, which was possibly from temporary extracranial compression such as increased transducer compression or anhydramnios/oligohydramnios.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…So far, only a few reports are similar to our case. 2,6,8,12,15 This reversed flow has been reported as a rare finding related to pathological fetal conditions, such as fetal growth restriction, 3,4,7,10,11,13 fetomaternal hemorrhage, 1,5,9 and congenital hydrocephalus. 14 Some cases had a transient period of reversed flow, which was possibly from temporary extracranial compression such as increased transducer compression or anhydramnios/oligohydramnios.…”
Section: Discussionmentioning
confidence: 95%
“…1 The majority of cases ultimately resulted in fetal or neonatal death. 1,2,4,[6][7][8]10,12,14,15 However, some studies reported that fetuses survived and subsequently required neurological follow-up; however, no study reported long-term neurological outcomes. 3,5,9,11,[13][14][15] A wide range of intervals between the diagnosis of reversed end-diastolic flow of the MCA and adverse event or delivery were reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations